Experience of stigma in the public life of relatives of people diagnosed with schizophrenia in the Republic of Belarus - Krupchanka, Dzmitry; Kruk, Nina; Sartorius, Norman; Davey, Silvia; Winkler, Petr; Murray, Joanna (Social psychiatry and psychiatric epidemiology, 2017)
PURPOSE: Mental health-related stigma affects people with mental disorders and their families. We aimed to investigate the experience of stigma among relatives of patients with schizophrenia in Belarus and formulate recommendations for anti-stigma interventions. METHODS: We conducted and thematically analysed 20 interviews with relatives of people diagnosed with schizophrenia. Experience of discrimination, strategies to cope with it, and requests for interventions were examined. RESULTS: A number of themes related to the experience of stigma in the public life of relatives of people with schizophrenia were elicited in relation to: (1) mental health care (difficulties in contacting mental health professionals; in getting appropriate information; lack of alternatives to hospital treatment; absence of appropriate long-term care services); (2) employment of people living with schizophrenia and (3) contact with the police. Analysis of the strategies used to overcome difficulties revealed resignation and passive acceptance, self-reliance, and emotional containment during crises. Despite the passivity and scepticism in expressing needs, participants suggested a number of interventions that could reduce the burden of stigma. CONCLUSIONS: With respect to the public domain of life, substantial stigma and discrimination perceived by families of people living with schizophrenia in Belarus is associated with structural issues of the country's mental health care system. To reduce the stigma-related burden, action must be taken to: (1) educate and support families and (2) deal with structural issues, by reorganising mental health services to better meet the needs of the families of people diagnosed with schizophrenia, and by including them in decision making at all levels.
Keywords: dospělí; Female; Mental health service; Social Stigma; rodina; Stigma; Adult; ženské pohlaví; Běloruská republika; Republic of Belarus; lidé; společenské stigma; schizofrenie; Family studies; Male; Aged; Schizophrenia; Eastern Europe; Family; lidé středního věku; senioři; mužské pohlaví; Middle Aged; Humans